Players’ Doctors: The Roles Should Be Very Clear - Caplan, Arthur L. (The Hastings Center report, 2016)
Years ago, one of us had the opportunity to talk with a starting guard in the National Basketball Association about his health care. The player, then a rookie, did not have his own personal doctor. Instead, he received his health care from the team doctor. This athlete was very well paid and could have received care anywhere he wished in the area. But he came from a very poor neighborhood. Growing up, he said, he had no health care other than hearing and eye tests done at his school and maybe (he was not sure) vaccinations given by the school nurse. The player said he now felt fine and trusted his team to look out for his health since they were paying him a lot of money and obviously wanted him on the court. While it might seem obvious that conflicts of role could arise for doctors working simultaneously for a team and for an athlete—wanting to please coaches, owners, and maybe fans while looking out for the athletes on the team—that is not how this young player saw things. He trusted his team and those who worked for them, and he figured that their interest in keeping him healthy overlapped nicely with his interest in staying healthy. As someone who did not get much access to health care as a child and had little need for it, he did not have concerns about conflicts of interest and second opinions foremost in his mind. But as is clear from a recent scandal involving the National Football League and concussion research, there are reasons for concern when athletes deal with health care workers paid by their teams.